The Role Of Women in The Work Forcecoffee Farming in Huta Ginjang Village Muara Distric Regency Of North Tapanuli - Silaban, Sartono; Tarumun, Suardi; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The research on the role of women in the workforce of coffee farming in Huta Ginjang village, Muara District, Regency of North Tapanuli have been done. The purpose of this study was to see how big the influence of social and economic factors on women's labor pouring in every stage of coffee farming jobs such as maintnance, harvesting and post-harvest. The method used in this study is survey method and simple regression analysis. Data and information collected in this study using primary and secondary data. Secondary data is data obtained from government agencies and the information obtained in the field while the primary data obtained directly from respondents by conducting interviews using a questionnaire tool. To see the outpouring of female labor in coffee farming is done through a multiple regression analysis with indicator used is hours of work, days of work, and labor standards. Furthermore analyzed using multiple linear regression analysis to see the impact of social and economic factors in the outpouring of coffe farming workers whether significant or effect is not significant. The results showed that the work of women involved in farming coffee work with father and children. However, the greatest percentage of time provided by Mother at 55,50 percent, followed by Father 34,75 percent and smallest given by children at 9,75 percent. Social factors remained influence but not significant on female labor force coffee farming means that just under 7,8 percent. Economic factors significant influence on coffee farming, meaning that the influence of economic factors above 67,7 percent in coffee farming. Keyword : Workforce, Farming, Women, Economic, Social.